The Effect of Dividend Policy on Corporate Financial Performance - Hermansyah, Aprilliyanti Melati Sukma (ADMAN: Journal of Contemporary Administration and Management, 2023)
Companies have many different objectives in running their operations. However, the main objective of the company is to maximise shareholder value. Firm value is the result of the company's performance in generating profits and minimising risks. For shareholders, the main benefit of share ownership is the dividends provided by the company. Research on the effect of dividend policy on the financial performance of companies in Indonesia is still relevant to be carried out in order to provide deeper insights for practitioners and academics in the field of finance. In this study, the author will describe the effect of dividend policy, as well as its relation to the company's financial performance, using a descriptive qualitative approach method. Based on the results of the research and discussion above, it can be concluded that dividend policy has a significant influence on the company's financial performance. However, this influence can be positive or negative depending on the conditions and factors that influence dividend policy.